Spontaneous Reporting Method Used for Safety Evaluation of Nonsteroidal Anti-Inflammatory Drugs and Paracetamol Products, Based on Assessment of Data from Periodic Reports - A. V. Matveev; E. A. Egorova; A. E. Krasheninnikov; E. I. Konyaeva (Безопасность и риск фармакотерапии, 2022)
High rates of adverse drug reactions (ADRs) associated with nonsteroidal anti-inflammatory drugs (NSAIDs), as well as their irrational and uncontrolled use for self-medication require continuous updating of information on safety profiles of these products.The aim of the study was to assess the reporting rate, frequency, and severity of ADRs to NSAIDs and paracetamol products, based on data from periodic safety update reports (PSURs) submitted to the autonomous non-profit organisation “National Pharmacovigilance Research Centre”.Materials and methods: the study covered 104 PSURs for NSAIDs and paracetamol products. Consumption levels were calculated in patient days (PTDs) and patient years (PTYs) for each international nonproprietary name (INN). The authors also analysed clinical manifestations and severity of ADRs.Results: the total number of PTDs and PTYs for all NSAIDs and paracetamol products, including combination medicines, was 1 963 750 485 PTDs or 5 380 138.3 PTYs, respectively. The PSURs reported 459 ADRs, of which 304 (66.2%) were serious ADRs (SADRs). The comparative analysis of ADR frequencies, expressed as the “ADR/PTY” ratio, for individual products, helped to identify INNs with the highest reporting rates.Conclusions: high ADR/PTY and SADR/PTY values indicating better ADR reporting for some INNs, were observed for piroxicam, paracetamol, dexketoprofen, and ketoprofen, while the lowest values were observed for the “acetyl salicylic acid+caffeine+paracetamol” combination, acetylsalicylic acid, and phenylbutazone. Thus, the comparison of ADR/PTY and SADR/PTY ratios can be recommended as an inclusive approach both for analysis of reporting trends for individual products and for comparison of reporting rates of different medicinal products.